Neuroptera of the Amazon basin. Part 11a. Introduction and chrysopint. - Adams, Phillip A.; Penny, Norman D. (Acta Amazonica, 1985)
33 species of Chrisopini are described and illustrated, of wich 30 are recorded from the Amazon Basin. Ten new species are described in Chrisopodes(duckei, spínella, nebulosa, lineafrons, polygonica, indetata, conisetosa, breviata, mediocris, and tetifera(, and nine in Ceraesochrysa(squalidens, acutipuppis, rafaeli, reddyi, nigripes, teneuícornis, ariasi, falceifera, and michaelmuris). Neosuarus (type species collaris (Schneider), a new subgenus of Chrysopodes, also contains divisa (Walker), escomeli (Navás) porterina (Navás), and flavescens (Blanchard). Orlandsia Navás and Ancylochrysa Navás are synonymized with Chrysopodes limbata (Navás), Chrysoperla asoralis (Banks) and Suarius nesotala (Banks). A neotype is designate for Ceraeochrysa cubana (Hagen). Ceraeochrysa caligata(Banks) and scapularis (Navás) are valid species. C. gloriae Alayo is synonymized with Ceraeochrysa everes (Banks).